Evolution of groundwater salinity and fluoride in the deep confined aquifers of Cangzhou in the North China plain after the South-to-North Water Diversion Project - Sun, Danyang; Li, Junxia; Li, Hexue; Liu, Qiang; Zhao, Shilin; Huang, Yihong; Wu, Qianyi; Xie, Xianjun (Applied geochemistry, 2022)
The South-to-North Water Diversion Project (SNWDP) has greatly improved the water shortage in the North China Plain. However, the impact of the SNWDP on the evolution of groundwater chemistry, especially fluoride and salinity, was still unknown. Cangzhou, one of the recipient cities of SNWDP and suffered from severe land subsidence, was selected to collect the deep confined groundwater samples before and after the SNWDP. The results showed that groundwater fluoride concentration decreased after the SNWDP, with a median value of 4.39 mg/L in 2017 and 3.00 mg/L in 2021, respectively. This trend was more clearly observed in the land subsidence area, which could be related to the reduction of land subsidence, due to the stopping pumping of deep groundwater. The pore water in clayey sediments contains fluoride up to 7.02 mg/L, which can be released into groundwater due to the sediment compaction before the SNWDP. The extensive exploitation during last decades changed the groundwater recharge patterns, resulting in over 60% deep groundwater being recharged by the pore water released from clayey sediment. The results of the Small Baseline Subset Interferometric Synthetic Aperture Radar (SBAS-InSAR) suggested that land subsidence has slowed down after the SNWDP, especially in the central area of land subsidence, thereby restricting the release of fluoride-rich pore water. However, groundwater salinity increased after the SNWDP, and the number of samples exceeding the drinking standard (TDS <1000 mg/L) increased by 26.4%. The rising groundwater level favors the water-rock interaction, promoting the dissolution of soluble minerals, for instance, halite, which was reflected by the results of inverse and forward modeling using the PHREEQC. Groundwater salinization after the SNWDP potentially induces the fluorite dissolution and causes the elevation of groundwater fluoride concentration. However, the calculated results indicate that the amount of F elevation related to groundwater salinization is significantly lower than the contribution of fluoride-rich pore water from clay sediment compaction. The findings of this study provide a comprehensive assessment of the influence of the SNWDP on the groundwater quality and some new insights for the management of groundwater resources. [Display omitted] •Groundwater F decreased and salinity increased in the Cangzhou after the SNWDP.•F concentration of pore water trapped in sediment was up to 7.02 mg/L.•The SNWDP restricts the release of pore-water preserved in the clayey sediment.•The elevation of groundwater F caused by salinization is less than caused by the release of F-rich pore water.